Production, organoleptic, and biological activities of belacan (shrimp paste) and pekasam (fermented freshwater fish), the ethnic food from the Malay archipelago - Khudair, Abedelazeez J. D.; Mohd Zaini, Nurul Solehah; Jaafar, Ahmad Haniff; Meor Hussin, Anis Shobirin; Wan-Mohtar, Wan Abd Al Qadr Imad; Abd Rahim, Muhamad Hafiz (National University of Malaysia Press, 2023)
Various popular fermented foods are produced commercially or at the household level. Chemical, physical, and microbiological changes may occur, either desirable or undesirable, in the food matrix during fermentation. Due to the scarcity of information in the literature regarding belacan (fermented shrimp) and pekasam (fermented freshwater fish) originating from the Malay Archipelago, this review will focus on the physiochemical changes, nutritional, microbiological, sensory, and biological activities of these food ingredients. Belacan is primarily composed of fermented blocks of shrimp with salt and usually is added as condiments in a small amount in cooking. In contrast, Pekasam consisted of freshwater fish in its original form, often fermented with ground toasted rice and natural acidulants, and can be used as the main dish. Both belacan and pekasam contain appreciable quantities of umami amino acids and 5′-ribonucleotides such as glutamate, inosinate, and guanylate from the protein degradation by both endogenous proteases and microbial growth. Unfortunately, the breakdown of proteins can contribute to the rise of biogenic amines, which can cause adverse effects on sensitive individuals. The growth of lactic acid bacteria is common, which is often considered safe, but spoilage microorganisms can easily contaminate the product in an unfavourable environment. Therefore, with rich nutrients and biological activities, the appropriate consumption of these food ingredients may contribute to better consumer health while increasing the acceptability of Malay traditional cuisines.